Investigating the mutual effects of autophagy and apoptosis in heart tissue of type 2 diabetic rats in interaction with aerobic exercise training and vitamin D3 injection - Hadi Golpasandi; Mohammad Rahman Rahimi; Slahadin Ahmadi (Shahid Beheshti University, 2024)
Background and Purpose: The interplay between autophagy and apoptosis is crucial in understanding heart health, particularly in the context of type 2 diabetes. The aim of this study was to investigate how aerobic training and vitamin D3 supplementation modulate the cardiac tissue of diabetic rats and highlight potential therapeutic strategies to improve cardiac function in diabetic conditions. Therefore, in this study, the effects of aerobic training and vitamin D3 injection on autophagy and apoptosis of heart tissue of diabetic rats were investigated.Materials and Methods: Forty male Wistar rats with a weight range of 200 - 240 grams were divided into two groups receiving a standard diet (8 rats) and a high-fat diet (32 rats) for 6 weeks. After 6 weeks, in order to induce type 2 diabetes, 35 mg/kg body weight of streptozotocin (STZ) was injected intraperitoneally. Rats receiving high-fat diet were randomly divided into 4 groups, diabetes control (DC), diabetes + aerobic training (DAT), diabetes + vitamin D3 injection (DVD) and diabetes + aerobic training + vitamin D3 injection (DVDAT). The rats in the aerobic training group underwent aerobic training with an intensity of 60% of the maximum running speed through a treadmill for eight weeks, 3 sessions/week in the aerobic training groups. The groups receiving vitamin D3 received a diluted solution of vitamin D3 with sesame oil at a dose of 10000 IU/kg weekly. After the completion of aerobic training interventions and vitamin D3 injection and anesthetizing the mice, the heart tissue was extracted and the protein levels of Beclin -1, Bax and Bcl -2 in the left ventricle of the heart tissue were measured by western blot technique. The data were analyzed using one-way analysis of variance (ANOVA).Results: Data analysis showed that type 2 diabetes increased the levels of Beclin-1, Bax and decreased Bcl-2 (P<0.001). Aerobic training, vitamin D3 and their interaction both decreased Beclin-1, Bax and increased Bcl -2, and that these changes were higher in the DVDAT group (P<0.001). The results also showed that fasting glucose levels and insulin resistance index decreased significantly in DAT, DVD and DVDAT groups (P<0.001), and this decrease was more in DVDAT group (P<0.001).Conclusion: In general, it could be concluded that type 2 diabetes causes disturbances in cellular and metabolic homeostasis, including insulin resistance, through increased autophagy and apoptosis in heart tissue, which can be reversed through aerobic training and vitamin D3, and improve glucose metabolism and insulin resistance.